Cardiac stroke volume in females and its correlation to blood volume and cardiac dimensions - Schierbauer, Janis; Ficher, Sandra; Zimmermann, Paul; Wachsmuth, Nadine B.; Schmidt, Walter F. J. (Frontiers in Physiology, 2022)
We aimed to continuously determine the stroke volume (SV) and blood volume (BV) during incremental exercise to evaluate the individual SV course and to correlate both variables across different exercise intensities. Twenty-six females with heterogeneous endurance capacities performed an incremental cycle ergometer test to continuously determine the oxygen uptake (V̇O2), cardiac output (Q̇) and changes in BV. Q̇ was determined by impedance cardiography and resting cardiac dimensions by 2D echocardiography. Hemoglobin mass and BV were determined using a carbon monoxide-rebreathing method. V̇O2max ranged from 32 to 62 mL·kg-1·min-1. Q̇max and SVmax ranged from 16.4 to 31.6 L·min-1 and 90 to 170 mL, respectively. The SV significantly increased from rest to 40% and from 40% to 80% V̇O2max. Changes in SV from rest to 40% V̇O2max were negatively (r=-0.40, p=0.05), between 40%-80% positively correlated with BV (r=0.45, p<0.05). At each exercise intensity, the SV was significantly correlated with the BV and the cardiac dimensions, i.e. left ventricular muscle mass (LVMM) and end-diastolic diameter (LVEDD). The BV decreased by 280 ± 115 mL (5.7%, p=0.001) until maximum exercise. We found no correlation between the changes in BV and the changes in SV between each exercise intensity. The hemoglobin concentration [Hb] increased by 0.8 ± 0.3 g·dL-1, the capillary oxygen saturation (ScO2) decreased by 4.0% (p<0.001). As a result, the calculated arterial oxygen content significantly increased (18.5 ± 1.0 vs. 18.9 ± 1.0 mL·dL-1, p=0.001). A 1 L higher BV at V̇O2max was associated with a higher SVmax of 16.2 mL (r=0.63, p<0.001) and Q̇max of 2.5 L·min-1 (r=0.56, p<0.01). In conclusion, the SV strongly correlates with the cardiac dimensions, which might be the result of adaptations to an increased volume load. The positive effect of a high BV on SV is particularly noticeable at high and severe intensity exercise. The theoretically expected reduction in V̇O2max due to lower SV as a consequence of reduced BV is apparently compensated by the increased arterial oxygen content due to a higher [Hb].